Strategi Pencegahan Fraud di Lingkungan Pelabuhan Indonesia - Safuan, Safuan (Politeknik Ganesha Medan, 2024)
The port is the gateway to a country's economy, so the port must be clean from fraud. The purpose of this study is to determine the strategy developed by Pelabuhan Indonesia to prevent fraud. The method used in this research is qualitative method with a case study approach. The results and conclusions of this study are many studies on fraud prevention in the Indonesian port environment, even though Indonesian ports are one of the entry points for global trade. Therefore, Indonesian ports need an efficient fraud prevention system. The study findings show that Indonesian ports have implemented two fraud prevention strategies. The first strategy is strengthening governance within Pelindo, which includes: a) ratifying GCG guidelines; b) carrying out the signing of an integrity pact; c) gratuity control; d) a violation reporting system called